The XXL Survey: XLII. Detection and characterisation of the galaxy population of distant galaxy clusters in the XXL-N/VIDEO field: A tale of variety - Trudeau, A; Garrel, C; Willis, J; Pierre, M; Gastaldello, F; Chiappetti, L; Ettori, S; Umetsu, K; Adami, C; Adams, N; Bowler, RAA; Faccioli, L; et al. (EDP Sciences, 2020)
Context. Distant galaxy clusters provide an effective laboratory in which to study galaxy evolution in dense environments and at early cosmic times. Aims. We aim to identify distant galaxy clusters as extended X-ray sources that are coincident with overdensities of characteristically bright galaxies. Methods. We used optical and near-infrared data from the Hyper Suprime-Cam and VISTA Deep Extragalactic Observations (VIDEO) surveys to identify distant galaxy clusters as overdensities of bright, zphot = 0:8 galaxies associated with extended X-ray sources detected in the ultimate XMM extragalactic survey (XXL). Results. We identify a sample of 35 candidate clusters at 0:80 = z = 1:93 from an approximately 4.5 deg2 sky area. This sample includes 15 newly discovered candidate clusters, ten previously detected but unconfirmed clusters, and ten spectroscopically confirmed clusters. Although these clusters host galaxy populations that display a wide variety of quenching levels, they exhibit well-defined relations between quenching, cluster-centric distance, and galaxy luminosity. The brightest cluster galaxies (BCGs) within our sample display colours that are consistent with a bimodal population composed of an old and red sub-sample together with a bluer, more diverse sub-sample. Conclusions The relation between galaxy masses and quenching seem to already be in place at z ~ 1, although there is no significant variation in the quenching fraction with the cluster-centric radius. The BCG bimodality might be explained by the presence of a younger stellar component in some BCGs, but additional data are needed to confirm this scenario.